Một số biện pháp dạy học chủ đề “Phương pháp tọa độ trong mặt phẳng” (Toán 10) nhằm phát triển năng lực giải quyết vấn đề trên môi trường số cho học sinh - Nguyễn Chí Thành, Nguyễn Chí Thành; Nguyễn Anh Thư, Nguyễn Anh Thư; Quách Thị Sen (Tạp chí Giáo dục, 2026)
In the context of digital transformation in education, developing problem-solving skills in a digital environment for students has become a crucial requirement in mathematics teaching. This research has identified a competency structure comprising four component competencies with 10 behavioral manifestations, and proposed two teaching methods for the topic “Coordinate Methods in the Plane” (Mathematics 10) to develop problem-solving skills in a digital environment for students. Through illustrative examples, the proposed methods create opportunities to develop problem-solving skills in a digital environment for students, especially in selecting, exploiting, adjusting, and evaluating the effectiveness of using digital tools to solve mathematical problems. This paper contributes to providing a theoretical basis and practical orientation for designing mathematics teaching activities that integrate digital tools with a competency-based approach. It also serves as a reference document for teachers in organizing teaching and learning activities to meet the requirements of the 2018 General Education Program and the trend of digital transformation in education.